2010
DOI: 10.1007/s10616-010-9324-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tetrahydrofuran, fetal calf serum, and Tween 40 for the delivery of astaxanthin and canthaxanthin to HepG2 cells

Abstract: The present investigation aimed to compare fetal calf serum (FCS) and Tween 40 with the commonly employed tetrahydrofuran (THF) with respect to cytotoxicity, stability of the solubilized carotenoids, and uptake and accumulation of the xanthophylls astaxanthin (AX) and canthaxanthin (CX) in cultured human liver cells (HepG2). Incubation of HepG2 cells for 24 h with THF (C1.25%) or FCS (C11.25%) with or without AX (C25 lmol/L) or CX (C25 lmol/L) did not affect cell viability. Tween 40 (0.25-1.25% in medium) redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…We first tried to deliver xanthophylls with the detergent Tween 40 [ 50 ]. We found that a higher concentration of Tween 40 (0.1%) led to HEK293F cell apoptosis as was previously described for HepG2 cells [ 51 ], while a lower concentration (0.01%) eluted mBCO2 from membranes during the Acyl-RAC assay even without hydroxylamine treatment (data not shown). Therefore, we established a new method to deliver xanthophylls without detergents using unilamellar LUVs as described above.…”
Section: Resultssupporting
confidence: 80%
“…We first tried to deliver xanthophylls with the detergent Tween 40 [ 50 ]. We found that a higher concentration of Tween 40 (0.1%) led to HEK293F cell apoptosis as was previously described for HepG2 cells [ 51 ], while a lower concentration (0.01%) eluted mBCO2 from membranes during the Acyl-RAC assay even without hydroxylamine treatment (data not shown). Therefore, we established a new method to deliver xanthophylls without detergents using unilamellar LUVs as described above.…”
Section: Resultssupporting
confidence: 80%
“…Even though THF is a toxic compound, THF (0.1%) did not decrease the cell viability of prostate cancer cell line DU145 and SH-SY5Y Neuroblastoma cell line SY5Y [73,74]. In addition, THF, up to the maximum concentration of 1.25% in the cell culture medium, did not affect the viability of the gastric cancer cell line HepG2 [75]. Therefore, 0.01% THF, used as control in the present study, may not affect cell viability.…”
Section: Discussionmentioning
confidence: 88%
“…For our cell studies, astaxanthin was dissolved in tetrahydrofuran (THF). We used THF since it has been previously shown by our group to be non-cytotoxic to HepG2 cells [ 31 ]. Furthermore, astaxanthin dissolved in THF exhibits an appropriate stability in the cell culture medium [ 31 ] and is effectively taken up by HepG2 and HT29 cultured cells [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%